Polymer quantum dots derived from poly (3, 4-ethylenediioxythiophene) and its applications for optical sensing - Chew, Huai Ping (2014)
The conventional commercially available fluorophores used to study & track biological activity suffer from several intrinsic drawbacks like rapid photo-bleaching making it difficult to carry out long-term imaging. Semiconductor QDs have been considered as alternatives but they may possess certain limitations such as poor photo-stability, cytotoxicity and carcinogenicity. Alternatively, a new breed of quantum dots derived from polymers possess certain advantages such as superior photostability, high biocompatibility, small size & tuneable optical properties thereby, promising them as superior substitutes for semiconductor QDs.